Fluorescence quenching of quantum dots with reactive oxygen species released from living cells - Chai, Jia Hao (2014)
One of the key bioapplication in quantum dots is the labeling of living cells. Quantum dots conjugated with 3-aminophenylboronic acid was modified from an amphipilic copolymer of maleic anhydride and octadecene coated quantum dots. These quantum dots were used to bind with macrophages via functional group conjugation. Macrophages were successfully labeled with these quantum dots that could be easily detected under a fluorescence microscope. The fluorescence could also be detected even as the quantum dots were internalized into the intracellular space allowing the observation and study of distributions and dynamics. In this project, we report a method to effectively release quantum dots from living cells. The effect of reactive oxygen species namely hydrogen peroxide and hypochlorous acid on quantum dots were studied. Hypochlorous acid was found to be much more effective than hydrogen peroxide and was selected and used to treat macrophages that had quantum dots bound on the cell membrane and also internalized by adding a trigger. The trigger which was phorbol 12-myristate 13-acetate was added to the solution which stimulated the cells to produce hypochlorous acid initiating a rapid quenching of quantum dots allowing complete release of the quantum dots from the living cells. These findings provide a ground support for quantum dots releasing which is an important factor for human in vivo application research in the future.